A Mendelian randomization study of genetic liability to cutaneous melanoma and sunburns - Lu, Fengmin; Wang, Ling; Ma, Xixing; Li, Yanling (Frontiers in Oncology, 2024)
BackgroundSome studies have reported that sunburns and cutaneous melanoma (CM) risk is increasing, but a clear causal link has yet to be established.MethodsThis current study conducted a two-sample Mendelian randomization (MR) approach to clarify the association and causality between sunburn history and CM using large-scale genome-wide association study data.ResultsThe inverse-variance weighted method result showed that sunburn might be associated with the risk of CM increasing (p = 2.21 × 10−23, OR = 1.034, 95% CI= 1.027-1.041), causally. The MR-Egger regression, weighted median method, simple mode method, and weighted mode method results showed similar results.ConclusionThis study offers evidence of sunburn history and increased risk of CM, and it shows that there might be common genetic basics regarding sunburns and CM susceptibility in Caucasian, European, or British ethnic groups.